1989
DOI: 10.1111/j.1467-1770.1989.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assessment of Foreign‐Language Skills: Implications for Teachers and Researchers

Abstract: Self-assessment accuracy is a condition of learner autonomy. If students can appraise their o w n performance accurately enough, they will not have to depend entirely on the opinions of teachers and, a t the same time, they will be able to make teachers aware of their individual learning needs. The purpose of this article is (1) to summarize the literature on self-evaluation of foreign language skills and (2) to show what it could mean to teachers and researchers. The conclusions of several self-assessment stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 7 publications
4
74
0
4
Order By: Relevance
“…Regarding self-assessment, teachers had been found to worry about implementing self-assessment, as they had doubts about learners' ability to assess their own proficiency accurately (Blanche & Merino, 1989). However, research showed that training helped (Brantmeyer & Vanderplank, 2012;Council of Europe, 2001), and accuracy increased when language was self-assessed with clear descriptors which were connected to the learning context, and items of abstract nature proved to be less accurate than functional (can do) skills (Butler & Lee, 2010;Harris, 1997).…”
Section: Teachers' Beliefs About Learner Autonomymentioning
confidence: 99%
“…Regarding self-assessment, teachers had been found to worry about implementing self-assessment, as they had doubts about learners' ability to assess their own proficiency accurately (Blanche & Merino, 1989). However, research showed that training helped (Brantmeyer & Vanderplank, 2012;Council of Europe, 2001), and accuracy increased when language was self-assessed with clear descriptors which were connected to the learning context, and items of abstract nature proved to be less accurate than functional (can do) skills (Butler & Lee, 2010;Harris, 1997).…”
Section: Teachers' Beliefs About Learner Autonomymentioning
confidence: 99%
“…In the last decade, with the increased attention to learner-centred curricula, needs analysis, and learner autonomy, the topic of self-assessment has become of particular interest in testing and evaluation (Blanche, 1988).Self-assessment is used by learners to evaluate and monitor their own level of knowledge, performance, and understanding and to get information about their learning (Dickinson, 1987). Therefore, self-assessment is what the students see from their own perspectives.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The more recent (Oscarson, 1989), comprehensive review suggests continued, marked diversity in the purposes, methods, and lines of inquiry subsumed under the" self-assessment" rubric (a theme which is reinforced by Oscarson's [forthcoming] review, based on examination of pre-publication copy, received too late for full consideration in this paper). For perspective regarding conceptual and methodological diversity see, for example, Ingram (1985), Bachman and Palmer (1989), Blanche and Merino (1989), Heilenman (1990), Xu (1991. For present purposes, it seems fair to say that in the field of second language proficiency assessment, interest in developing and evaluating formal self-assessment "instruments" has not been widespread, and very few studies appear to have employed the same or clearly similar instruments/models.…”
Section: Je Connais Presque La Totalite De La Grammaire Anglaise Maimentioning
confidence: 99%